The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2196/19375
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Enablers in Implementing Electronic Consultations in Primary Care: Scoping Review

Abstract: Background Often promoted as a way to address increasing demands, improve patient accessibility, and improve overall efficiency, electronic consultations are becoming increasingly common in primary care, particularly in light of the current COVID-19 pandemic. However, despite their increasing use, a theoretically informed understanding of the factors that support and inhibit their effective implementation is severely limited. Objective With this scoping… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 24 publications
3
45
4
1
Order By: Relevance
“…The implementation of remote consultations in the form of text messages and telephone and video appointments has been ramped up significantly in recent years [1][2][3]. Telehealth has been shown to be a useful alternative to face-to-face appointments and has advantages for patients, health practitioners and the environment [1][2][3][4][5][6]. Today the use of remote consultations is omnipresent across medical specialities, a process greatly accelerated by the coronavirus disease 2019 (COVID-19) pandemic [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The implementation of remote consultations in the form of text messages and telephone and video appointments has been ramped up significantly in recent years [1][2][3]. Telehealth has been shown to be a useful alternative to face-to-face appointments and has advantages for patients, health practitioners and the environment [1][2][3][4][5][6]. Today the use of remote consultations is omnipresent across medical specialities, a process greatly accelerated by the coronavirus disease 2019 (COVID-19) pandemic [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Telehealth has been shown to be a useful alternative to face-to-face appointments and has advantages for patients, health practitioners and the environment [1][2][3][4][5][6]. Today the use of remote consultations is omnipresent across medical specialities, a process greatly accelerated by the coronavirus disease 2019 (COVID-19) pandemic [2,[6][7][8]. The Royal College of General Practitioners and other similar bodies have recently reiterated that remote consultations will form a fundamental role in future care delivery and emphasize the need for ongoing research and investment into telehealth to optimise both the provision of care and the patient experience [7,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reviews have not reported design or implementation details of the OCs they studied (e.g. [18][19][20]), despite their importance in understanding the causal mechanisms of how they impact outcomes [48]. In this paper, we systematically review and synthesise the empirical quantitative and qualitative literature in a theoretically-informed way to address this knowledge gap.…”
Section: Introductionmentioning
confidence: 99%